Монгол Улсын олон тулгуурт гадаад бодлого Хятадын аюулгүй байдалд нөлөөлөх нь - Дазүнь, Ли; Зеньпин, Жан; Синь, Ван (Journal of International Studies, 2005)
English title: Multipolar foreign policy of Mongolia and its influence on the security of China translated by B.Indra